Spirituality and adjustment: The role of identity - Li, Shengnan (Journal of spirituality in mental health, 2020)
The study examined the relationship between spirituality, identity development, and maladjustment variables. A total of 1,016 college student participants (53.9% female) were recruited from a major state university in the southern United States, the structural equation modeling revealed that aspects of identity development mediated the relationship between certain aspects of spirituality (spiritual transcendence, spiritual search, and spiritual function) and certain maladjustment variables (existential anxiety, identity distress, and internalizing symptoms). Identity exploration and identity commitment items appeared to have some unique relationships with the other variables, as did the various aspects of spirituality. Implications for measurement and future research are discussed.